No bidirectional relationship between inflammatory bowel disease and diverticular disease: a genetic correlation and Mendelian randomization study - Aierken, Ailikamu; Atabieke, Falide; Aierken, Munire; Li, Jian; Xia, Yu; Aizezi, Yierzhati; Li, Shui-Xue (Frontiers in Genetics, 2024)
Background: Although previous studies found that inflammatory bowel disease (IBD) and diverticular disease (DD) usually co-exist clinically, studies examining the relationship are spare. Aim: Our study aspires to investigate the causal correlation between the IBD [including ulcerative colitis (UC) and Crohn’s disease (CD)] and DD using the Mendelian randomization (MR) analysis. Methods: We conducted a two-sample bidirectional MR analysis using publicly available genome-wide association studies (GWAS) summary data. The single nucleotide polymorphism (SNP) data associated with DD and IBD were obtained from the Finnish Biobank and UK Biobank, respectively. Through secondary data analysis of all GWAS summary data, we systematically screened genetic instrumental variables. To address the impact of horizontal pleiotropy, several methods were employed, including the inverse variance-weighted method (IVW), maximum likelihood method, Egger regression method, weighted median method, and simple median method. These approaches aimed to detect and correct for the potential bias caused by horizontal pleiotropy. Results: Genetically predicted DD did not have a causal effect on IBD (OR 1.06, 95% CI 0.98–1.17, p = 0.15), and had no causal effect on UC (OR 1.10, 95% CI 0.94–1.20, p = 0.36) and CD (OR 1.03, 95% CI 0.92–1.16, p = 0.62) either. Furthermore, in the reverse MR analysis, we did not observe any significant causal effect of IBD on DD. Results of complementary methods showed consistent results with those of the IVW method. Conclusion: This study’s findings do not provide evidence for a causal relationship between IBD and DD, which contradicts the majority of observational studies.